1999
DOI: 10.1161/01.cir.99.15.1984
|View full text |Cite
|
Sign up to set email alerts
|

Kallidin- and Bradykinin-Degrading Pathways in Human Heart

Abstract: Background-Since kinins kallidin (KD) and bradykinin (BK) appear to have cardioprotective effects ranging from improved hemodynamics to antiproliferative effects, inhibition of kinin-degrading enzymes should potentiate such effects. Indeed, it is believed that this mechanism is partly responsible for the beneficial effects of angiotensin-converting enzyme (ACE) inhibitors. In the heart, enzymes other than ACE may contribute to local degradation of kinins. The purpose of this study was to investigate which enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Bradykinin and kallidin peptides may also be metabolized by different enzymes. Kokkonen et al 37 report that kallidin metabolism by cardiac membranes is via aminopeptidase M-like activity, whereas bradykinin is metabolized by NEP.…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin and kallidin peptides may also be metabolized by different enzymes. Kokkonen et al 37 report that kallidin metabolism by cardiac membranes is via aminopeptidase M-like activity, whereas bradykinin is metabolized by NEP.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the human myocardial interstitium, NEP represents the major bradykinin degrading enzyme. 2 Along with the renin-angiotensin system (RAS) and the sympathetic nervous system, the kallikrein-kinin system is involved in the onset and progression of heart failure and ventricular remodeling after myocardial infarction. 3 Kinins reduce left ventricular hypertrophy and fibrosis and prevent progression of heart failure.…”
mentioning
confidence: 99%
“…NEP, a membrane-bound M13 zinc metallopeptidase, was first detected in the brush border of animal kidney by Kerr and Kenny (1974). Since then, NEP presence has been described in many vascular tissues, such as rat aorta smooth muscle, adventitial and endothelial cells (Gonzá lez et al, 1998), human endothelial cells (Llorens-Cortes et al, 1992), and cardiomyocytes (Kokkonen et al, 1999). Gafford et al (1983) have shown that the selective BKB 2 receptor agonist BK is hydrolyzed by NEP.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme has been described in endothelial cells of many origins (Erdos, 1990), in human heart (Kokkonen et al, 1999), and in rat aorta smooth muscle (Arnal et al, 1994). ACE cleaves the C-terminal tripeptide from BKB 1 receptor agonists, yielding BK 1-5 but at a slower rate and with less affinity than the removal of the C-terminal dipeptide from BK (Marceau et al, 1998).…”
Section: Discussionmentioning
confidence: 99%